Case studies in object-oriented analysis and design - Yourdon, Edward (Prentice Hall, 1996)
This book is great. It starts from a description of the case studies and it ends with the implementation. With this book, you can make your first object oriented project a good one with ease! A must have for a beginner on object-oriented projects. I've tried other books, but none compared to this.